Church Container (study in physical geography) - Qassem Al-Tai, Ghaida Saeed; Al-Mohsen, Isbahiya Younis (Journal of Tikrit University for Humanities, 2022)
The study of the Hawi alkaneesa-(church container) is a study of natural geography where the area of the study is determined between two latitude (-12-36 north) with a longitude (-18-36 E) and is located in a semi-dry region characterized by dry and wet months. And this is why Geomorphological processes contrast here. The Hawi area is located on the right side of the city of Mosul at the Monastery of St. Michael to the north, and bordered from the east by the Tigris River, which aligns the area of Musherafah and extends south to Fault Wadi Akkab. The geology of the study area has been identified in terms of its geological formation. It dates back to the Middle Meiosis era, the sedimentary deposits, the four-era deposition and the deposition of the flood plain. The study area is located on a large water resource, the Tigris River, which is used to irrigate industrial projects, drinking and household purposes. n this study, we rely on the analysis of the geological forms of the land cover based on spatial Landsat scanner (MSS) , Digital Elevation Model DEM and its conformity with the topographic map, and the study of land slopes based on the Zink1989 classification of the area of Hawi Al kaneesa. The study revealed the relationship between geomorphological geological units in terms of concentration, soil, slope, and terrestrial susceptibility of the church’s area which is (10.393.453 km2) of the right side of the city of Mosul in order to know the region’s qualifications and obstacles, in addition to human investments:(Agricultural-pastoral – quarries) The research confirmed a set of conclusions and proposals reached by researchers which gave scientific precision to the research